2010
DOI: 10.1073/pnas.1004996107
|View full text |Cite
|
Sign up to set email alerts
|

Severe anemia in theNanmutant mouse caused by sequence-selective disruption of erythroid Krüppel-like factor

Abstract: Studies of mouse models of anemia have long provided fundamental insights into red blood cell formation and function. Here we show that the semidominant mouse mutation Nan (“neonatal anemia”) carries a single amino acid change (E339D) within the second zinc finger of the erythroid Krüppel-like factor (EKLF), a critical erythroid regulatory transcription factor. The mutation alters the DNA-binding specificity of EKLF so that it no longer binds promoters of a subset of its DNA targets. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

26
140
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(166 citation statements)
references
References 49 publications
26
140
0
Order By: Relevance
“…Remarkably, an ethylnitrosourea-induced mutation in the homologous position in mouse KLF1 causes the dominant Nan (neonatal anemia) phenotype. [16][17] Heterozygous Nan/+ mice displayed hereditary spherocytosis and severe hemolytic anemia. Expression of erythrocyte membrane skeleton proteins and β-globin was reduced, but embryonic globins were present at aberrantly high levels (Figures 1 and 3).…”
Section: Klf1 Mutations In Humans -Congenital Dyserythropoietic Anemiamentioning
confidence: 99%
See 2 more Smart Citations
“…Remarkably, an ethylnitrosourea-induced mutation in the homologous position in mouse KLF1 causes the dominant Nan (neonatal anemia) phenotype. [16][17] Heterozygous Nan/+ mice displayed hereditary spherocytosis and severe hemolytic anemia. Expression of erythrocyte membrane skeleton proteins and β-globin was reduced, but embryonic globins were present at aberrantly high levels (Figures 1 and 3).…”
Section: Klf1 Mutations In Humans -Congenital Dyserythropoietic Anemiamentioning
confidence: 99%
“…The mutation, p.E339D, reduced binding to a subset of KLF1 binding sites, and this selectively affected activation of KLF1 target genes. 17 The variant residues have opposite charges: positive in the CAD patients (p.E325K, lysine) and negative in the Nan mouse (p.E339D, aspartic acid). These mutants have different DNA binding properties that determine the impact on the expression of KLF1 target genes.…”
Section: Klf1 Mutations In Humans -Congenital Dyserythropoietic Anemiamentioning
confidence: 99%
See 1 more Smart Citation
“…23 The ethylnitrosurea-induced mouse mutant Nan (neonatal anemia) carries a missense mutation, p.E339D, in the homologous position of mouse KLF1. 39,40 This mutation causes a dominant hemolytic anemia, with markedly increased expression of embryonic globins in adult Nan animals. 40 Collectively, these data support a model in which KLF1 activates b-globin expression and suppresses the embryonic/fetal b-like globin genes.…”
mentioning
confidence: 99%
“…39,40 This mutation causes a dominant hemolytic anemia, with markedly increased expression of embryonic globins in adult Nan animals. 40 Collectively, these data support a model in which KLF1 activates b-globin expression and suppresses the embryonic/fetal b-like globin genes. Recently, it has been shown that expression of BCL11A is regulated by KLF1, suggesting an intricate mechanism for the developmental regulation of the b-like globin genes coordinately mediated by KLF1 and BCL11A.…”
mentioning
confidence: 99%